Linear Demand Systems are Inconsistent with Discrete Choice - Jaffe, Sonia; Weyl, E. Glen (B. E. Journal of Theoretical Economics (Advances), 2010)
We show that with more than two options, a discrete choice model cannot generate linear demand. In doing so, we demonstrate a prediction of such discrete choice models that is falsifiable based on local second-order properties of demand.